(untitled) (Confluenţe Bibliologice, 2016)
The article highlights Vasile Alecsandri’s correspondence with various cultural and political people . Today, Vasile Alecsandr’si correspondence is considered as unique in Romania culture.The article highlights Vasile Alecsandri’s correspondence with various cultural and political people . Today, Vasile Alecsandr’si correspondence is considered as unique in Romania culture.